Analisis faktor yang berhubungan dengan kejadian phlebitis pada pasien yang terpasang infus di ruang medikal chrysant Rumah sakit awal bros pekanbaru - Agustini, Chandra -; Utomo, Wasisto -; -, Agrina - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research intends to analyze and find out about factors of phlebitis incidence for infused patient. For that purpose, this research use correlation description as research method and cross sectional as observation method. This research is conducted in Chrysant Medical Hospitalization room, Awal Bros Hospital, Pekanbaru by involving 92 respondents, using purposive sample as sampling method, and observation sheet as measuring instrument. The method of analysis used in this research is both univariate and bivariate data. The result of this test analysis research shows that there is relationship between age and intravenous fluids towards phlebitis with significant influence p value = 0.000, in which elderly and hypertonic fluids affect the phlebitis. Meanwhile, dressing and morbidities are not associated significantly by phlebitis with p value = 0.643 and p value = 1.00. The result of this research is expected to be reference for hospital, particularly for medical personnel in order to keep consistent implementing procedure and policy ever been applied to prevent phlebitis incidence. Key words: phlebitis, age, fluid, dressing, and morbidities. References: 45 (2000-2013)